MANUFACTURING SITE LOUHAN FISH WITH MICROSOFT FRONTPAGE 2000 - Danu Rahman; Sahni Damerianta P, SKom, MMSI (Jurnal Sistem Informasi, 2003)
One that makes attractive a site with beautiful objects in the contents of the site, using Microsoft frontpage 2000 and with manufacturing sites louhan fish are expected to add insight on this louhan fish. Making this louhan fish site presents 10 drawings and description louhan fish.